100+x/5=-10x+-10x-1

Simple and best practice solution for 100+x/5=-10x+-10x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 100+x/5=-10x+-10x-1 equation:



100+x/5=-10x+-10x-1
We move all terms to the left:
100+x/5-(-10x+-10x-1)=0
We add all the numbers together, and all the variables
x/5-(-20x-1)+100=0
We get rid of parentheses
x/5+20x+1+100=0
We multiply all the terms by the denominator
x+20x*5+1*5+100*5=0
We add all the numbers together, and all the variables
x+20x*5+505=0
Wy multiply elements
x+100x+505=0
We add all the numbers together, and all the variables
101x+505=0
We move all terms containing x to the left, all other terms to the right
101x=-505
x=-505/101
x=-5

See similar equations:

| -19+12x-10x=-18 | | 7.1x-4.7=62.3 | | (3x+8)^2=64 | | 28–x=3x | | .9(90)=20+16p | | 6x+1/2x+(-1/2)=-(1/2) | | 20+16p=81 | | 12x-34=8x+15 | | -5=n/3 | | (3x+8)2^=64 | | 2x+9+3x+3x=3x+1 | | 2x+9+3x+3x=2x+8 | | 2x+9+3x+3x=2x+7 | | 2x+9+3x+3x=2x+6 | | 2x+9+3x+3x=2x+5 | | 2x+9+3x+3x=2x+4 | | 2x+9+3x+3x=2x+3 | | 2x+9+3x+3x=2x+2 | | 2x+9+3x+3x=2x+1 | | 2x+9+3x+3x=1x+9 | | 2x+9+3x+3x=1x+8 | | 2x+9+3x+3x=1x+7 | | 2x+9+3x+3x=1x+6 | | 2x+9+3x+3x=1x+5 | | 2x+9+3x+3x=1x+3 | | 2x+9+3x+3x=1x+2 | | 2x+9+3x+3x=1x+1 | | 2x+9+3x+3x=1x+4 | | 5y+11=30 | | 2x+9+3x+3x=2x+9 | | x/2+x/2+x/2+(-18)=10x-1 | | -13-(-27)=x/11 |

Equations solver categories